2019
DOI: 10.1080/14616696.2019.1616791
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of ethnocentrism in Europe. A comparison of enduring and emerging determinants of solidarity towards immigrants

Abstract: This article examines cross-national differences in solidarity towards immigrants in the EU. This concept of solidarity is operationalized through perceived ethnic threat vs. a positive view of multicultural society. The main argument of this article is that 'classical' enduring determinants (sociodemographic factors, subjective values and structural factors) are still able to explain ethnocentrism, but these factors are enriched and mediated by a cluster of five emerging explanatory factors which reflect soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…A second direction for future research is to corroborate the findings in a different context as this study was conducted in The Netherlands. We believe that the current pattern of results will be similar for many Western societies, because similar relationships between, for example, anti-refugee attitudes and societal discontent have been found in other (European) countries (Aschauer & Mayerl, 2019;Rooduijn, 2017). We therefore expect that across European countries, anti-refugee protests will be predicted by societal discontent and refugee intergroup threat.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 54%
“…A second direction for future research is to corroborate the findings in a different context as this study was conducted in The Netherlands. We believe that the current pattern of results will be similar for many Western societies, because similar relationships between, for example, anti-refugee attitudes and societal discontent have been found in other (European) countries (Aschauer & Mayerl, 2019;Rooduijn, 2017). We therefore expect that across European countries, anti-refugee protests will be predicted by societal discontent and refugee intergroup threat.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 54%
“…In recent years scholars have started analysing the stability of solidarity during crises and following such events. Aschauer and Mayerl (2019) found that social solidarity is likely to decrease during societal malaise, narrowing down the circle to which solidarity is confined. Other studies argued that periods of crisis are expanding the coverage of those worthy of solidarity and showed how crises can lead to increasing creativity in the manifestations of solidarity (Forno and Graziano 2019;Koos and Siebel 2019).…”
Section: Value Change Collective Events and Corona Crisismentioning
confidence: 99%
“…Solidarity has a long history as a key concept in the social sciences (Lahusen and Grasso 2018a;Koos 2019) and in the European history, playing a significant role in the development of welfare states post-World War II, in the development and expansion of the European Union (EU) (Dragalov et al, 2016), being under scrutiny during recent societal crises (Aschauer and Mayerl 2019;Forno and Graziano 2019;Gerhards et al 2019;Koos 2019) and, even more recently, in Europe's response to the Corona crisis. After two decades of almost complete freedom of movement within the EU, the economic recession at the end of the 2000s and the Corona crisis have led to borders being reinvented.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the effect of societal malaise is expected to vary with different welfare arrangements. Using survey data from 21 EU countries, Aschauer and Mayerl (2019) first show, that the perception of crisis decreases from the Southern and Eastern European countries to the Northern European countries. Next, using multi-group structural equation models the authors illustrate how societal malaise has a strong effect on exclusive social solidarity mediating the effect of structural, individual and socio-demographic determinants.…”
Section: Contributions In the Special Issuementioning
confidence: 99%
“…Fourthly, crises affect the scope of solidarity. Thus, as Aschauer and Mayerl (2019) have shown societal malaise leads to more exclusionary group boundaries. More generally, the perception of some societal malaise moderates the effect of socio-economic conditions for exclusionary solidarity.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%